2016
DOI: 10.5897/ajmr2016.7956
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic bacteriuria: Occurrence and antibiotic susceptibility profiles among students of a tertiary institution in Ile-Ife, Nigeria

Abstract: Asymptomatic bacteriuria, a form of urinary tract infections that involves isolation of a specified quantitative count of bacteria in an appropriately collected urine specimen obtained from a person without symptoms or signs referable to urinary infection is common, but the prevalence in population varies widely with age, sex and the presence of genitourinary abnormalities. This study therefore aimed at investigating the prevalence of asymptomatic bacteriuria among selected students of Faculty of Pharmacy, Oba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…In line with previously documented results [1, 3, 11] our study revealed, female participants had seven folded increased risk of acquiring UTI. This might be due to females have short, wider and direct urethra, lack of prostatic fluid which acts as antimicrobial; and having warm and moist urethra which could be supportive for the optimal growth of bacteria compared to males [37].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In line with previously documented results [1, 3, 11] our study revealed, female participants had seven folded increased risk of acquiring UTI. This might be due to females have short, wider and direct urethra, lack of prostatic fluid which acts as antimicrobial; and having warm and moist urethra which could be supportive for the optimal growth of bacteria compared to males [37].…”
Section: Discussionsupporting
confidence: 93%
“…This was in line with findings reported from the general population in Ethiopia (22.5%) [46] and (22%) [47]. This could be as CoNS are a normal flora of the urogenital area at puberty, which may invade the urinary tract during sexual activity especiallyinfemales [1]. Isolation rate of S.aureus (13.5%) and K.pneumoniae (.1%) in our study was comparable to previous reports in Nigeria (13.3%) and (6.4%)respectively [37].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The costs of treatment of the UTI are high, with previous studies from France and the US reporting €58 million and $2.47 billion; respectively, for treatments of the UTIs (Foxman et al, 2000;François et al, 2016). UTIs occur when the bacterial pathogen enters into different parts of the urinary tract system, including the urethra; bladder, ureter, and kidneys, and its load may reach more than 10 5 cells\ ml in urine (Osungunna and Adeyemi, 2016). The prevalence of UTIs is influenced by the age; sex, comorbidities, and functional abnormalities in the lower urinary tract (Byron, 2018).…”
Section: Introductionmentioning
confidence: 99%